1989
DOI: 10.1002/j.1460-2075.1989.tb08598.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and sequencing of the protein-tyrosine kinase substrate, ezrin, reveals homology to band 4.1.

Abstract: Ezrin is a component of the microvilli of intestinal epithelial cells and serves as a major cytoplasmic substrate for certain protein‐tyrosine kinases. We have cloned and sequenced a human ezrin cDNA and report here the entire protein sequence derived from the nucleotide sequence of the cDNA as well as from partial direct protein sequencing. The deduced protein sequence indicates that ezrin is a highly charged protein with an overall pI of 6.1 and a calculated molecular mass of 69,000. The cDNA clone was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
171
0
2

Year Published

1992
1992
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(175 citation statements)
references
References 55 publications
2
171
0
2
Order By: Relevance
“…Three peptide sequences were obtained and were found to be identical to the ERM protein moesin (Table I). The peptide sequences are inconsistent with those of the closely related proteins ezrin (17), radixin (18), merlin/schwannomin (19,20), or talin (21).…”
Section: Properties Of the Partially Purifiedmentioning
confidence: 80%
“…Three peptide sequences were obtained and were found to be identical to the ERM protein moesin (Table I). The peptide sequences are inconsistent with those of the closely related proteins ezrin (17), radixin (18), merlin/schwannomin (19,20), or talin (21).…”
Section: Properties Of the Partially Purifiedmentioning
confidence: 80%
“…bases with the zyxin protein sequence were performed and revealed that zyxin is not identical to any protein or derived amino acid sequence currently deposited in these databases. In addition, we specifically examined the possibility that zyxin might be related to cytoskeletal proteins such as ezrin (Gould et al, 1989;Turunen et al, 1989), radixin (Funayama et al, 1991), moesin (Lankes and Furthmayr, 1991), protein kinase C (Ono et al, 1986;Knopf et al, 1986), the calcium dependent protease (Aoki et al, 1986), plakoglobin (Franke et al, 1989), the MARCKS protein (Graft et al, 1989), and gelsolin (Kwiatkowski et al, 1986) that exhibit a similar molecular mass on SDS-polyacrylamide gels; we found no significant sequence relationship between zyxin and any of these proteins. Based on analysis of the deduced amino acid sequence of zyxin, the predicted unmodified pI of the protein is 7.04, a value that is consistent with the observed pI of zyxin which ranges from 6.4-7.2 (Crawford and Beckerle, 1991).…”
Section: Predicted Amino Acid Sequence Of Zyxinmentioning
confidence: 86%
“…Those authors subsequently showed that radixin is highly concentrated at the cleavage furrow in a variety of culture cells during cytokinesis, which implies that radixin might modulate the actin filament-plasma membrane interaction at the furrow (Sato et al, 1991). The subcellular localization of ezrin and its sequence homology to protein 4.1 and talin suggested that ezrin also connects plasma membrane and actin-based cytoskeleton (Gould et al, 1989). Although a great deal of effort has been spent to verify such an hypothesis, only recently have Louvard and his colleagues shown that the N-terminal half of ezrin determines the plasma membrane association whereas the C-terminal half is responsible for actin-cytoskeletal association, as judged by immunocytochemistry and detergent extraction as well as cytochalasin D treatment (Algrain et al, 1993).…”
Section: Discussionmentioning
confidence: 99%